The Essential Guide to Open Source Flash Development - Allen, Chris; Arnold, Wade.; Balkan, Aral.; Cannasse, Nicolas; Grden, John.; Gunesch, Moses; Hughes, Marc.; MacDonald, R. Jon.; Zupko, Andy.; SpringerLink (Online service) (Berkeley, CA : Apress, 2008)
Explore the world of open source Flash and discover which tools are available. Learn how to identify which tool you need and how to best fit it into your workflow. Step-by-step walk-throughs guide you through development with the most popular open source Flash tools. Written by the project leads and open source Flash aficionados. The Essential Guide to Open Source Flash Development is a practical development guide to creating Flash applications with open source Flash tools and workflows. You will walk away with an understanding of what tools will best suit your current situation, making your development easier and more productive, and with the knowledge of how to install and set up some of the best tools available, including the following: Papervision3D: to create 3D in Flash Red5: to stream video over the internet SWX: to build data-driven mashups and mobile apps Fuse: to make ActionScript animation a cinch Go: to build your own animation tools in ActionScript 3.0 haXe: to create Flash files and more AMFPHP: to communicate between Flash and php Open source Flash has been a revolution for Flash and has made a major impact on how people build Flash content. The open source tools available expand on Flash's existing tool set, enabling you to perform such tasks as easily create full 3D in Flash or hook up to an open source video-streaming server. Many of these useful tools are powerful yet lack documentation. this book explains in step-by-step detail how to use the most popular open source Flash tools. If you want to expand your Flash tool set and explore the open source Flash community, then this book is for you. If you already use some open source Flash tools, then you will find this book a useful documentation resource as well as an eye-opener to the other tools that are available.
Introducing the World of Open Source Flash -- ExPloring Open Source Flash: What$1 (BS Available -- Preparing an Open Source Workflow -- Using an Open Source Workflow -- Testing and Debugging -- Deploying Your Application -- Using AMFPHP -- Working with SWX: The Native Data Format for the Flash Platform -- Using HaXe -- Fuse and Goasap: Open Source Animation Tools -- Using Papervision3D -- Introducing Red5 -- Building Some Red5 APPS.s
Keywords: Computer science; Software engineering; Computer Science; Software Engineering/Programming and Operating Systems; Electronic books